A Novel Smooth Super-Twisting Control Method for Perturbed Nonlinear Double-Pendulum-Type Overhead Cranes - Shehu, Muhammad A.; Li, Aijun (Arabian journal for science and engineering (2011), 2021)
The double-pendulum (DP) phenomenon, effectuated by the fact that the payload configuration and the chain length between the hook and the payload are usually unknown, is a typical issue in actual cranes. This phenomenon is considered in the current study to enhance tracking accuracy and sway regulation for overhead cranes subject to perturbations and multiple frictions. A novel smooth super-twisting algorithm hybridized with the integral sliding mode control (ISMC) is proposed to solve the problems. The closed-loop system’s finite time stability has been examined using a strict quadratic Lyapunov function. Compared to an existing modified super-twisting algorithm (MSTC), it has been shown that the proposed algorithm mitigates both the sliding surface overshoot and the initial peaking of the control effort that can be encountered using the MSTC algorithm. Furthermore, simulation experiments and error analysis show improved effectiveness of the proposed technology against the existing MSTC and the conventional ISMC technologies. The paper contribution primarily dwells on devising a novel structure of super-twisting algorithm that ensures the nonlinear perturbed DP overhead crane’s desired performance.